Laparoscopic EndoClose fixation of a peritoneal catheter reduces migration. Issue 1 (30th November 2019) - Rouse, Michael; Choi, Julian; Bakhit, Jacqueline; Soh, Brian; Chan, Steven
Abstract: Background: With the introduction of laparoscopic Tenckhoff catheter insertion in the early 1990s, catheter malposition resulting in malfunction remains a frequent complication, often requiring surgical or radiological intervention. In this pioneer study, we describe the technique of suturing the Tenckhoff catheter using an EndoClose (Medtronic, Macquarie Park, NSW, Australia) device to the anterior abdominal wall during laparoscopic insertion and compare its outcomes with those not sutured. Methods: This is a retrospective study of all patients who underwent laparoscopic Tenckhoff catheter insertion at Western Health from January 2013 to June 2018. All procedures were undertaken or supervised by one surgeon. The primary outcome was catheter malposition requiring surgical revision. Secondary outcomes were time to malposition and complications. Peri‐ and post‐operative factors were analysed to adjust for confounders using the Cochran–Mantel–Haenszel test. Results: There were 82 patients in the sutured group and 63 patients in the non‐sutured group. Catheter malposition occurred in 7.32% in the sutured group and 19.05% in the non‐sutured group ( P = 0.034; 95% confidence interval for the difference 0.007–0.237). There was an overall reduction in the odds of catheter malposition of 63% in favour of the sutured group. The median time‐to‐malposition was 128 and 182 days for the non‐sutured and sutured group, respectively, but not statistically different. No differences were found for the number of post‐operative complications. Conclusion: Suturing of Tenckhoff catheter with an EndoClose device to the anterior abdominal wall during laparoscopic insertion is a simple, safe and useful method of reducing catheter malposition. Abstract : Using EndoClose device to secure the peritoneal catheter, reduces migration. It is a safe procedure which allows easy removal without general anaesthetic if required.